The Relationship Between Shoulder Arm Muscle Power and the Ability to Punch the Court Tennis Drive in Students of the 2022 FKIP USK Physical Education Study Program - Syamsulrizal Syamsulrizal; Masyita Siregar; Muhammad Iqbal; Liasar Liasar; Arfi. R; Fajar Fajar; Yunadi Yunadi (Journal on Education, 2024)
Field observations obtained when I was on the committee of the Field Tennis League (LITEL) from these players stated that to achieve high tennis achievements, supported by good physical, technical, tactical and mental conditions, especially when hitting drives on sportsmen is a requirement that cannot be neglected, especially the game of court tennis. This type of research can be classified under Descriptive research as stated by Arikunto (1991: 63) that "Descriptive research. The number of samples in this study was 31 Penjaskesrek students. Data collection techniques in this study were Measurement of Power Ability of shoulder arm muscles and Measurement of Agility of Stroke Drive Tennis Court. The calculation of the correlation coefficient value above can be concluded that arm muscle power with the ability to punch the court tennis drive in FKIP USK Physical Education Students has a significant relationship. The results of the data calculation, showed that the correlation coefficient value (r) between the power of the shoulder arm muscles and the ability to punch the court tennis drive in FKIP USK Penjaskesrek Students was 0.50. In the sport of field tennis, the Drive punch is one of the basic techniques that must be mastered in the game of court tennis.